Efektivitas Model Pembelajaran Problem Posing Setting Think Pair Share pada Materi Bangun Ruang Sisi Datar terhadap Kemampuan Berpikir Kritis dan Kepercayaan Diri - Mardiah, Ainun (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to determine the effectiveness of the problem-posing learning model with the Think Pair Share (TPS) setting on flat-sided solid geometry material in relation to students' critical thinking skills and self-confidence. The study employs a pretest-posttest control group experimental design. The sample was randomly selected, followed by a pretest to measure initial abilities and a posttest to evaluate learning outcomes. The research instruments include lesson plans (RPP), student worksheets, pretest and posttest critical thinking tests, as well as a self-confidence questionnaire. Data were analyzed using a t-test for critical thinking skills and the Mann-Whitney test for self-confidence. The results show that the TPS learning model is more effective than conventional teaching methods in improving students' critical thinking skills and self-confidence in the flat-sided solid geometry material at SMP 23 Sinjai. Based on pretest data for critical thinking skills and self-confidence between the experimental and control classes, no significant average differences were observed. However, posttest analysis results indicate significant values of 0.021 for critical thinking and 0.002 for self-confidence, both of which are less than 0.05. This indicates that the problem-posing learning model with the TPS setting is more effective than conventional methods in enhancing students' critical thinking skills and self-confidence